Artifact-free recordings in human bidirectional brain-computer interfaces - Weiss, Jeffrey M; Flesher, Sharlene N; Franklin, Robert; Collinger, Jennifer L; Gaunt, Robert A (Journal of neural engineering, 2019)
Objective. Intracortical microstimulation has shown promise as a means of evoking somatosensory percepts as part of a bidirectional brain-computer interface (BCI). However, microstimulation generates large electrical artifacts that dominate the recordings necessary for BCI control. These artifacts must be eliminated from the signal in real-time to allow for uninterrupted BCI decoding. Approach. We present a simple, robust modification to an existing clinical BCI system to allow for simultaneous recording and stimulation using a combination of signal blanking and digital filtering, without needing to explicitly account for varying parameters such as electrode locations or amplitudes. We validated our artifact rejection scheme by recording from microelectrodes in primary motor cortex (M1) while stimulating in somatosensory cortex of a person with a spinal cord injury. Main results. M1 recordings were digitally blanked using a sample-and-hold circuit triggered just prior to stimulus onset and a first-order 750 Hz high-pass Butterworth filter was used to reduce distortion of the remaining artifact. This scheme enabled spike detection in M1 to resume as soon as 740 µs after each stimulus pulse. We demonstrated the effectiveness of the complete bidirectional BCI system by comparing functional performance during a 5 degree of freedom robotic arm control task, with and without stimulation. When stimulation was delivered without this artifact rejection scheme, the number of objects the subject was able to move across a table in 2 min under BCI control declined significantly compared to trials without stimulation (p  <  0.01). When artifact rejection was implemented, performance was no different than in trials that did not include stimulation (p  =  0.621). Significance. The proposed technique uses simple changes in filtering and digital signal blanking with FDA-cleared hardware and enables artifact-free recordings during bidirectional BCI control.